MODEL KONSEPTUAL HUMAN-CENTERED LEADERSHIP BERBASIS EMPATI UNTUK MENINGKATKAN LOYALITAS DAN PRODUKTIVITAS JANGKA PANJANG - Rida Justin Jacobalis (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
The increasing complexity of multinational organizations demands leadership approaches that move beyond structural control and short-term performance orientation. This article develops a conceptual model of human-centered leadership by positioning empathic leadership as a strategic relational foundation for sustainable organizational productivity. Integrating emotional intelligence theory, self-determination theory, and organizational commitment theory, the study proposes a sequential mediation framework in which empathic leadership enhances employee well-being, well-being strengthens affective loyalty, and loyalty ultimately drives long-term productivity. Unlike prior studies that examine direct or partial relationships between leadership and performance, this article introduces a multi-layered mechanism explaining how leadership influence unfolds through psychological and relational processes. The model reconceptualizes empathy not merely as an interpersonal competency, but as organizational relational capital that bridges individual psychological conditions and sustainable performance outcomes. Theoretically, this study contributes by integrating emotional, motivational, and commitment-based perspectives into a unified human-centered leadership framework. Practically, it offers strategic guidance for multinational organizations seeking to enhance long-term competitiveness through employee-centered leadership. Future empirical research is encouraged to test the proposed sequential mediation model across industries and cultural contexts.